Design and Building of an Automated Lighting Control System for Rooms Based on Internet of Things (IoT) - Winda Erika; Herdianto; Abdur Rahim Firmansyah; Muhammad Ridho Sukri (Yayasan Sinergi Multidimensi Kreatif, 2024)
The development Internet of Things (IoT) technology has been widely used in daily life, especially in the use of electronic devices in homes, such as lights. To create an automatic lighting control system for a room from a distance, a PIR (Passive Infrared Receiver) sensor is needed as input to turn the light on and off automatically based on movement detected in the room. To control the light automatically and connect the devices to the internet, the ESP8266 is used. The results show that the PIR (Passive Infrared Receiver) sensor can detect movement within the room. Thus, the automatic lighting control system can be monitored remotely using a smartphone.